2005
DOI: 10.1093/humrep/dei045
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in vitro maturation and expression of LH receptor in cumulus cells of the oocytes collected from PCOS patients in HCG-primed IVM cycles

Abstract: These results suggest that the presence of dispersed CCs at oocyte collection may be positively correlated with the rates of oocyte maturation and blastocysts in HCG-primed IVM cycles. In addition, the expression of LH receptor in CCs may be correlated with the CC pattern of oocytes at collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 32 publications
1
37
1
5
Order By: Relevance
“…Further studies confirmed that even though the leading or dominant follicle was recruited, the administration of HCG did not affect the quality of oocytes retrieved from the follicles of smaller size [Chian et al 2002;Chian et al 2004]. In a previous study, we also demonstrated the existence of LH/HCG receptor in the cumulus cells from the small follicles when the HCG-priming IVM treatment cycles were performed for patients with PCOS [Yang et al 2005]. …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Further studies confirmed that even though the leading or dominant follicle was recruited, the administration of HCG did not affect the quality of oocytes retrieved from the follicles of smaller size [Chian et al 2002;Chian et al 2004]. In a previous study, we also demonstrated the existence of LH/HCG receptor in the cumulus cells from the small follicles when the HCG-priming IVM treatment cycles were performed for patients with PCOS [Yang et al 2005]. …”
Section: Discussionmentioning
confidence: 53%
“…Even though there are LH/HCG receptors in the cumulus and granulosa cells from the relatively small follicles [Yang et al 2005;Jin et al 2005], it is not clear how the small follicles react to the physiological LH surge. Clearly, it is important to determine the time of HCG injection in the natural cycle IVF/M treatment in order to retrieve more mature oocytes from the leading follicles.…”
Section: Discussionmentioning
confidence: 99%
“…An association between LH receptor expression and expanded CC morphology was reported in PCOS patients (Yang et al, 2005). In addition, in several animal species, it has been shown that CC LH/ hCGR mRNA was positively correlated to CC expansion and oocyte maturation, but did not change during IVM (Calder et al, 2003(Calder et al, , 2005Fu et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…LH/hCGR mRNA expression was also observed in CCs from patients with polycystic ovarian syndrome (PCOS) who received hCG before oocyte recovery for in vitro maturation (IVM) and LH/hCGR expression correlated with the degree of oocyte maturation (Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several genes downstream of GDF9 have been correlated with oocyte quality. Among these HAS2, GREM1 and PTSG2 [10,43,60]. Therefore, gene expression in cumulus cells can be a useful predictor of oocyte quality.…”
Section: Discussionmentioning
confidence: 99%